2022
DOI: 10.1097/rlu.0000000000004162
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of 18F-PSMA-1007 PET/CT in Detection of Metastatic Renal Cell Carcinoma to the Brain

Abstract: 18F-PSMA PET/CT is an emerging standard of care in staging prostate cancer, evaluating biochemical recurrence and response to therapy. Despite the nomenclature, PSMA expression is also documented at the tumor-associated neovasculature of other malignant solid tumors including renal cell carcinoma. We report a case of 44-year-old man known to have renal cell carcinoma who underwent 18F-PSMA and 18F-FDG PET/CT for restaging after radical nephrectomy. A well-defined solitary cerebellar lesion with marked PSMA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Radiofrequency ablation, cryoablation and high-energy focused ultrasound are the three main minimally invasive treatments. Among them, radiofrequency ablation is the most widely used because of its early application and mature technology ( 7 ). Unlike partial nephrectomy, radiofrequency ablation does not need to block the renal artery, nor does it cause intraoperative renal ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency ablation, cryoablation and high-energy focused ultrasound are the three main minimally invasive treatments. Among them, radiofrequency ablation is the most widely used because of its early application and mature technology ( 7 ). Unlike partial nephrectomy, radiofrequency ablation does not need to block the renal artery, nor does it cause intraoperative renal ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Conversely from [ 18 F]F-FDG, PSMA radioligands do not have uptake in the healthy brain parenchyma and might play a role in the study of malignancies that metastasize in this district, increasing the accuracy in the staging or restaging compared with the conventional imaging and [ 18 F]F-FDG PET/CT. 3,[5][6][7] As we reported in this case, recent articles described abnormal uptake of PSMA-targeting radiopharmaceuticals in the setting of primary lung tumors [8][9][10] ; furthermore, a recent study observed that PSMA expression in the vasculature of primary lung carcinomas has been associated with faster metastatic dissemination to the brain. 11 To the best of our knowledge, this is the first report of accidental finding of brain metastases from lung adenocarcinoma with [ 18 F]F-PSMA-1007 PET/CT.…”
supporting
confidence: 66%
“…Nevertheless, recent immunohistochemistry studies revealed that PSMA, also known as glutamate carboxypeptidase type II, is expressed by the neovascular endothelial cells of primitive and metastatic lesions of various solid tumors, including gliomas 3,4. Conversely from [ 18 F]F-FDG, PSMA radioligands do not have uptake in the healthy brain parenchyma and might play a role in the study of malignancies that metastasize in this district, increasing the accuracy in the staging or restaging compared with the conventional imaging and [ 18 F]F-FDG PET/CT 3,[5][6][7]. As we reported in this case, recent articles described abnormal uptake of PSMA-targeting radiopharmaceuticals in the setting of primary lung tumors[8][9][10] ; furthermore, a recent study observed that PSMA expression in the vasculature of primary lung carcinomas has been associated with faster metastatic dissemination to the brain 11.…”
mentioning
confidence: 99%
“…[4][5][6] The patient was enrolled in a clinical trial of PSMA PET in tumors of urinary system approved by the institutional review board of our hospital. 18 F-PSMA-1007 PET/CT was performed 4 hours after abdominal contrast-enhanced CT. [7][8][9][10][11] 1,12 Von Hippel-Lindau syndrome is a rare autosomal-dominant hereditary tumor disease that arises owing to germline mutations in the VHL gene. 12 Patients with von Hippel-Lindau syndrome are at risk of developing various benign and malignant tumors, including retinal and central nervous system hemangioblastomas, endolymphatic sac tumors, pancreatic cysts, cystadenomas and neuroendocrine tumors, pheochromocytomas, renal cysts and clear cell renal cell carcinomas, and epididymal and broad ligament cystadenomas.…”
Section: Figurementioning
confidence: 99%
“…The patient was enrolled in a clinical trial of PSMA PET in tumors of urinary system approved by the institutional review board of our hospital. 18 F-PSMA-1007 PET/CT was performed 4 hours after abdominal contrast-enhanced CT [7][8][9][10][11]. MIP PET (A) showed a focal intense activity (arrowhead) in the nasal region and 2 focal activity (straight arrows) in the scrotal region.…”
mentioning
confidence: 99%